Analysis on Students’ Understanding of Hydrocarbon Compounds in Organic Chemistry II Course - Kriesna Kharisma Purwanto (EduChemia (Jurnal Kimia dan Pendidikan), 2021)
Hydrocarbon material is one of the organic chemical materials which is the basic concept for studying the next organic chemistry concept. Based on the result of observation, the average score of students in Organic Chemistry I course is 67.89. The result of this study indicates that students have difficulty of understanding in organic compounds. The objective of this research is to analyze the understanding on chemistry education students of hydrocarbon compounds in Organic Chemistry II course. The research design in this research is descriptive quantitative. The research subjects are students of the 2017 Chemical Education study program. There are 3 stages in the research, including pretest, implementation of learning, and posttest. The pretest aims to obtain data on students' initial knowledge of the material to be studied. Implementation of learning aims to improve students' understanding of hydrocarbon compound material, while posttest aims to measure the level of understanding of students after being given treatment. The conclusion of thisstudy is the students have highest difficulty in the topic hydrocarbon reactions (67.75%).